The clinical syndrome of dystonia with anarthria/aphonia - Ganos, Christos; Crowe, Belinda; Stamelou, Maria; Kresojević, Nikola; Lukić, Milica Ječmenica; Bras, Jose; Guerreiro, Rita; Taiwo, Funmilola; Balint, Bettina; Batla, Amit; Schneider, Susanne A.; Erro, Roberto; et al. (Parkinsonism & related disorders, 2016)
In dystonia the formulation of a clinical syndrome is paramount to refine the list of etiologies. We here describe the rare association of dystonia with anarthria/aphonia, by examining a large cohort of patients, to provide a narrow field of underlying conditions and a practical algorithmic approach to reach diagnosis. We retrospectively reviewed cases, which were evaluated between 2005 and 2014, to identify those with dystonia combined with marked anarthria and/or aphonia. We reviewed demographic information, clinical characteristics, as well as clinico-genetic investigations. We evaluated video material where available. From 860 cases with dystonia as the predominant motor feature, we identified 32 cases (3.7%) with anarthria/aphonia. Age at neurological symptom onset was variable, but the majority of cases (n = 20) developed symptoms within their first eight years of life. A conclusive diagnosis was reached in 27 cases. Monoamine neurotransmitter disorders, neurodegeneration with brain iron accumulation syndromes, hypomyelination with atrophy of the basal ganglia and cerebellum, and syndromes with inborn errors of metabolism were the most common diagnoses. Brain MRI was crucial for reaching a diagnosis by examining the structural integrity of the basal ganglia, the cerebral cortex, brain myelination and whether there was abnormal metal deposition. Pathophysiological mechanisms underlying anarthria/aphonia included dystonia, corticobulbar involvement, apraxia and abnormalities of brain development. The spectrum of conditions that may present with the syndrome of dystonia with anarthria/aphonia is broad. Various causes may account for the profound speech disturbance. A practical brain MRI-based algorithm is provided to aid the diagnostic procedure. •To describe the spectrum of conditions presenting with dystonia and anarthria/aphonia.•From 860 cases with dystonia, we identified 32 (3.7%) with anarthria/aphonia.•Most cases (n = 20) developed symptoms within their first eight years of life.•A conclusive diagnosis was reached in 27 cases.•An algorithmic approach to reach a diagnosis based on brain MRI is provided.